Pengaruh Brand Image , Gaya Hidup dan Lokasi Terhadap Keputusan Pembelian: Studi Kasus Es Teh Badak Pandeglang - Rt.Sri Ratna Ayu Kamillah; Robby Hernanada; Ela Nuramalia; Riki Gana Suyatna (Lembaga Pengembangan Kinerja Dosen, 2024)
Purchasing decisions are a crucial stage in the marketing process that is influenced by a number of factors. brand image (product image), lifestyle, and location have become important aspects that play a significant role in shaping consumer preferences Badag Ice Tea in Pandeglang will provide deep insight into how these elements interact with each other and contribute to consumer purchasing decisions. This type of research is quantitative with the aim of tracking the impact between independent factors (autonomous variables) and reliant variables (subordinate variables). the research place is Es Teh Badag Pandeglang. the research time was conducted for approximately 3 months from November 2023 to January 2024.The results of this study indicate that the f test of brand image, lifestyle and location simultaneously and significantly affects the purchasing decision of badag ice tea in pandeglang. The t test results show that brand image, lifestyle and location have a positive and significant influence on purchasing decisions for badag ice tea in pandeglang. The R2 value of 0.609 or 60.9% means that the brand image, lifestyle and area factors have an impact of 60.9% on purchasing decisions, the excess 39.1% is influenced by factors outside the focus such as value, progress and service quality.